Noncoagulating Enteral Formula Can Empty Faster From the Stomach: A Double‐Blind, Randomized Crossover Trial Using Magnetic Resonance Imaging. (3rd April 2014) - Kuyumcu, Sena; Menne, Dieter; Curcic, Jelena; Goetze, Oliver; Klebach, Marianne; Abrahamse, Evan; Hofman, Zandrie; Fried, Michael; Schwizer, Werner; Steingoetter, Andreas
Abstract : Background: The gastric accumulation of enteral formulas in tube‐fed patients leads to an increased risk of vomiting and regurgitation. Gastric secretion–induced coagulation of proteins in enteral formulas might lead to gastric accumulation of solid protein particles that further increase the risk of upper digestive intolerance. This study used magnetic resonance imaging to noninvasively assess the half‐emptying time (t50 ) of enteral formulas differing in protein composition. Methods : Three isocaloric (450 kcal) and isovolumetric (300 mL) enteral formulas, 1 with a noncoagulating P4 protein blend and 2 with coagulating casein‐dominant protein blends, were compared in a double‐blind, randomized, 3‐way crossover study in 21 healthy volunteers. Gastric content emptying curves were fitted with the LinExp model to compute t50 and the parameter κ with κ > 1 reflecting the accumulation of gastric secretion. t50 and κ were compared between all 3 enteral formulas. The formula that emptied fastest was identified by an ordinal mixed model using the ranks of t50 . Results : As indicated by values for κ > 1, all enteral formulas induced gastric secretion. No differences were detected for t50 . However, the noncoagulating formula emptied fastest in 74% of all participants ( P = .004). Conclusion : This study demonstrates that a noncoagulating enteral formula can empty faster from the stomach compared with coagulating formulas in a large cohort of healthy volunteers. Investigations on the efficiency of the noncoagulating P4 protein blend in patients requiring tube feeding will further elucidate its potential for reducing upper digestive intolerance during enteral nutrition. Trial NTR2979.